1999
DOI: 10.1002/(sici)1097-0290(19990220)62:4<479::aid-bit11>3.3.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Selenium reduction by a denitrifying consortium

Abstract: A denitrifying bacterial consortium obtained from the Pullman, Washington wastewater treatment facility was enriched under denitrifying conditions and its ability to reduce selenite and selenate was studied. Replicate experiments at two different experimental conditions were performed. All experiments were performed under electron-acceptor limiting conditions, with acetate as the carbon source and nitrate the electron acceptor. In the first set of experiments, selenite was present, whereas, in the second set, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Lee et al (2007) reported that facultative anaerobic Shewanella species, well known for their capability to generate electricity in MFCs, were able to utilize selenite as the sole electron acceptor for respiration in anaerobic conditions, resulting in reduction of selenite and precipitation of elemental Se nano-sized spherical particles. Denitrifying bacteria, which could play an important role in electron transfer in the MFCs (Sukkasem et al 2008), were also reported capable of reducing selenite or selenate to elemental Se (Rege et al 1999). By using these electrogens, simultaneous electricity generation and COD/Se removal can be achieved, indicating the great potential of using MFC technology for wastewater treatment.…”
Section: Selenite Removalmentioning
confidence: 99%
“…Lee et al (2007) reported that facultative anaerobic Shewanella species, well known for their capability to generate electricity in MFCs, were able to utilize selenite as the sole electron acceptor for respiration in anaerobic conditions, resulting in reduction of selenite and precipitation of elemental Se nano-sized spherical particles. Denitrifying bacteria, which could play an important role in electron transfer in the MFCs (Sukkasem et al 2008), were also reported capable of reducing selenite or selenate to elemental Se (Rege et al 1999). By using these electrogens, simultaneous electricity generation and COD/Se removal can be achieved, indicating the great potential of using MFC technology for wastewater treatment.…”
Section: Selenite Removalmentioning
confidence: 99%
“…Antipov et al (2000) have found that V(V) reduction follows nitrate consumption, and that the process is associated with some structural reorganizations of nitrate reductase. Rege et al (1999) have reported that selenate and selenite reduction occurs after a lag period, during which a seleniumreducing population was stimulated or the needed enzyme was produced in the existing denitrifying population. In the present research, there was still a lag time for Ni(II) reduction with NH 4 + -N instead of NO 3 − -N, and the Ni(II) reduction efficiency had no remarkable difference (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to limitations of analytical methodology, as well as to the low concentrations of selenium species in municipal wastewater. Rege et al (1999) investigated selenate and selenite reduction capability in batch reactors inoculated with a mixed consortium obtained from a wastewater treatment plant. It was observed that biomass possessed the ability to reduce both selenate and selenite to elemental selenium.…”
Section: Mercurymentioning
confidence: 99%